Musyrifah's Efforts to Guide the Morals of Santriwati at the Al-Amien Tegal Prenduan Islamic Boarding School, Sumenep, Madura in 2023 - Mawaddah Mawaddah; Afifah Afifah (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2025)
Cases of juvenile delinquency increase every year, so the solution is character formation through education and a conducive environment. This has received special attention in the world of Islamic boarding schools through moral development efforts, such as those carried out by the Al-Amien Tegal Prenduan Islamic Boarding School, Sumenep, Madura. This thesis uses descriptive qualitative methods, with data collection techniques, namely interviews, observation and documentation. The focus of the research is divided into two, namely Musyrifah's efforts to guide female students' morals and the supporting and inhibiting factors. The findings from this research are that there are several efforts made by Musyrifah to guide female students' morals both in theory and practice. Meanwhile, the supporting factors are cooperation, coordination and support both between musyrifah and from the caregivers and guardians of the students. And the inhibiting factor is the difference in the background of the female students.